Personal intelligence relationship with the management agliation among teachers (Journal of the College of Education for Women, 2019)
Personal intelligence is thinking about an other person , understanding him, have sympathy and differentiation between people, and to appreciate their own point of view, with the sensitivity to their motives, behavior, and goals, so this intelligence involves dealing with a person or group of persons effectively and in normal or logical manner. Emotions management is to achieve emotional balance by controlling the emotions continuously, self disciplining, keeping away from excitement sources, and dealing with bad situations in constructive way to achieve the psychological stability . the study aims to :The level of Personal Intelligence for Teachers .The level of Emotions Management for Teachers .The Statistical relationship between personal intelligence and emotions managementThe Statistical relationship between personal intelligence and emotions management according to the variables of gender and social state.